Tiempo, futuro y mente: la conciencia acompañante y la anticipación del futuro - Quintero, Juan Pablo (Pontificia Universidad Católica del Perú, 2024)
This paper examines the subjective foundations of time perception. It explores Husserl’s idea of time as an intimate experience and permanent flow. Along the way, speculations are ventured about the philosophical tradition prone to establish indissoluble links between consciousness, knowledge of time, and imagination. The common thread is the correlation that exists in the human experience of time based on the mental succession of the triad composed of the past, present and future. If human identity is constituted by recollections and anticipations of past and future experiences, then one might wonder to what extent subjective impressions of the temporal flow are the basic foundation of self-perception, the self, and of any introspective gaze. Considerations on the effects of temporality on consciousness and on the construction of the self are also included.

Este artículo indaga sobre el fundamento subjetivo de la percepción del tiempo. El abordaje propuesto recorre la idea husserliana del tiempo como experiencia íntima y flujo permanente. En el camino se aventuran especulaciones sobre la tradición filosófica inclinada a establecer vínculos indisolubles entre la conciencia, el conocimiento del tiempo y la imaginación. El hilo conductor es la correlación existente en la experiencia humana del tiempo a partir de la sucesión mental de esa triada compuesta por el pasado, presente y futuro. Si la identidad humana se compone de procesos de memoria y la anticipación del futuro, entonces cabría preguntarse hasta qué punto las impresiones subjetivas del flujo temporal son fundamento básico de la autopercepción, el yo y cualquier mirada introspectiva. También se incluyen consideraciones sobre los efectos de la temporalidad en la consciencia y la construcción del yo.
Keywords: Mind; Husserl; Time; Memory; Consciousness; Future; Imagination; Fantasy; Mente; Husserl; Tiempo; Memoria; Conciencia; Futuro; Imaginación; Fantasía; https://purl.org/pe-repo/ocde/ford#6.03.01